FIQH PEREMPUAN, KEKINIAN DAN KEINDONESIAAN (Telaah Kritis Membangun Fiqh Berkeadilan Gender) - Ipandang Ipandang (LPPM IAIN Parepare, 2015)
Fiqh is a product of the dialectic between text, context and objectivity-subjectivity of a faqih. One of fiqh’s product is legal rules of women’s live. Most of the scholars who produce ijtihad in fiqh are men. Jurisprudence which is set out by men as dominant society such in the Middle East region, of course will produce patriarchy fiqh. Now it is a time to renew and to reconstruct Islamic concepts that give women more opportunity to be present as a highly dynamic person, courteous and helpful person to the religion and society. Women are not as human who are confined to four walls of house, every day just walking to the room, kitchen, and well.